Drei für Slowenien neue Schmetterlings-Arten aus den Gattungen Caloptilia, Catoptria und Earias (Lepidoptera: Gracillariidae, Pyralidae Crambinae und Noctuidae) - Habeler, Heinz (Acta entomologica slovenica (Ljubljana), 2010)
On the mount Slavnik in the region of Podgorski Kras in Slovenia one specimen of a taxon near to Catoptria spatulella was found. More specimens are needed to confirm its identity as C. spatulella, endemic to Italy - or to document a new Catoptria species. Also in the Podgorski Kras in the surroundings of Črnotiče one specimen of Caloptilia loriolella was found and one of Earias insulana, a little green species of the Noctuidae known from South Europe.
Keywords: entomologija; favna; metulji; Podgorski Kras; Slovenia; Slovenija